Network pharmacology-based investigation into the mechanism of action of Tongxie Yaofang decoction in the treatment for ulcerative colitis - Yuyi MAI; Yujian LIN; Jun SHI; Mengyue REN; Fang WANG (KeAi Communications Co., Ltd., 2021)
[Abstract]: Objective: Network pharmacology techniques were used to predict the key active compounds and targets of Tongxie Yaofang decoction in treating ulcerative colitis (UC) and exploring the potential multicomponent, multitarget, and multipathway mechanism. Also, peroxisome proliferator-activated receptor-γ (PPAR-γ) in cancer pathways was selected for animal testing. Methods: The chemical components of the four herbs in Tongxie Yaofang decoction were collected from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP), whereas the other relevant information was obtained from the literature. Targets of the active compounds were obtained from the TCMSP and Swiss Target Prediction. Meanwhile, the UC targets were searched and screened from GeneCards and DisGeNET and intersected with targets of the active compounds in Tongxie Yaofang decoction. The obtained common targets were imported into the STRING database to build the target protein-protein interaction network. Cytoscape software was used to construct the network diagram of single herb-active compounds-targets of Tongxie Yaofang decoction. The common targets of the drug and disease received the Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis to determine the biological functions and metabolic pathways of the drug and predict its potential mechanism of action in treating UC. Molecular docking was conducted for the top 3 and 5 relevant proteins using AutoDock software and verified in animal testing: UC rat models were established and received 22 g/kg alcohol extract of Tongxie Yaofang decoction through intragastric administration for 28 days. The colonic mucosa damage index was assessed. PPAR-γ protein expression was detected by immunohistochemistry. Results: Fifty-three UC-related potential active compounds and 168 potential targets were obtained. Paeoniflorin in Radix Paeoniae Alba and wogonin in Radix Sileris might be the key compounds of Tongxie Yaofang decoction in treating UC. Cyclooxygenase-2 (PTGS2), the most highly associated with active compounds, might be an important therapeutic target. GO and KEGG enrichment analyses showed that the efficacy of Tongxie Yaofang decoction involved various molecular functions and biological processes and might achieve the collaborative treatment for UC through multiple pathways, such as cancer pathways, tumor necrosis factor signaling pathway, Toll-like receptor signaling pathway, and phosphatidylinositol 3-kinase/Akt signaling pathway. The molecular docking results demonstrated that active compounds had a favorable binding activity with the target AR. Tongxie Yaofang decoction could significantly increase PPAR-γ expression in UC rats (P < 0.05), verifying part of the predicting outcomes of network pharmacology. Conclusion: Tongxie Yaofang decoction is featured with the multicomponent, multitarget, multipathway collaborative treatment for UC. This study has predicted the potential active compounds and key targets and preliminarily clarified the potential material base for the efficacy and mechanism of this drug.